Tackling the critical question of Schooling’s NS deferment after his poor Tokyo Olympics performance - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
In a commentary, SMU Associate Professor of Law Eugene Tan, who was team manager of Singapore’s 2004 Athens Olympics national swim team, discussed the critical question of Singapore’s sporting icon Joseph Schooling’s National Service (NS) deferment after his subpar performance at the Tokyo Olympics. Joseph has been on long-term NS deferment since 2014. Assoc Prof Tan noted that what is at stake is the integrity of long-term deferment, and the precedent-setting decision calculus which would come under intense scrutiny.